A meta-analysis study on the attitudes of pre-service music teachers towards the teaching profession in Turkey - Rasim Erol Demirbatır; Zeynep Özer (Intelektual Pustaka Media Utama, 2021)
The objective this study was to determine whether music teacher candidates’ attitudes towards the teaching profession in Turkey differ with respect to different variables. In this direction, a meta-analysis study was carried out on the pre-service music teachers’ attitudes towards their profession. The study consists of 12 studies chosen with predetermined criteria. Since the effect sizes of these studies display a heterogeneous structure, the random effects model was conducted. Effect sizes in the random effects model were calculated by using Hedges g coefficient with 12 studies for gender and nine studies for the form of high school graduated. Taking the results of the findings into consideration, it was concluded that the attitudes of female music teacher candidates towards the teaching profession are more positive than male candidates. There is no difference between Fine Arts and other high schools regarding the variable of the form of high school.